2003
DOI: 10.1039/b212610a
|View full text |Cite
|
Sign up to set email alerts
|

Metallomesogens by ligand design

Abstract: In this Perspective, some of the basic principles of ligand design will be described as they apply to the synthesis of metal complexes with liquid crystal properties. Liquid crystal properties of metal complexes are a delicate function of both ligand and metal and examples will be chosen to illustrate this statement. In particular, the effect of the metal complex moiety on the mesomorphism of a series of imine and diimine liquid crystals is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(71 citation statements)
references
References 90 publications
2
67
0
Order By: Relevance
“…In this context, aromatic carboxylate ligands, and especially N-heterocyclic carboxylates, have been intensively studied for their versatile coordination modes and potential applicability to different fields, pharmaceutical, catalyst and magnetic properties and others. These studies are extensively reported in the literature [1][2][3][4][5][6][7][8]. As a part of our continuing investigations on inorganic-organic hybrid compounds containing zinccarboxylate systems, the title complex was synthesized.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, aromatic carboxylate ligands, and especially N-heterocyclic carboxylates, have been intensively studied for their versatile coordination modes and potential applicability to different fields, pharmaceutical, catalyst and magnetic properties and others. These studies are extensively reported in the literature [1][2][3][4][5][6][7][8]. As a part of our continuing investigations on inorganic-organic hybrid compounds containing zinccarboxylate systems, the title complex was synthesized.…”
Section: Discussionmentioning
confidence: 99%
“…IR spectra were recorded on a Bruker spectrophotometer using KBr discs. 1 H and 13 C NMR spectra were recorded on a Bruker spectrometer operating at 500 MHz, using CDCl 3 as solvent. 1 H chemical shifts were referenced to the solvent peak position, δ 7.26 ppm.…”
Section: Characterization Methodsmentioning
confidence: 99%
“…1 H and 13 C NMR spectra were recorded on a Bruker spectrometer operating at 500 MHz, using CDCl 3 as solvent. 1 H chemical shifts were referenced to the solvent peak position, δ 7.26 ppm. e phase assignments for the BTU ligand and its copper(I) complexes were evaluated by polarizing optical light microscopy (POM), placed on untreated glass slides, using a Nikon 50iPol microscope equipped with a Linkam THMS600 hot stage and TMS94 control processor.…”
Section: Characterization Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure consists of ionic units: [AgL] 2 2þ and [PF6 ] À .The crystalline structure of 2 also contains four molecules of solvent: two of 1,2-dichloroethane and two of diethyl ether with a high disorder (see Experimental section). The structure consists of a bimetallic Ag(I) complex where metallic centres are connected via k 2 -N,P to two ligands in a head-to-face arrangement generating an homobimetallic macrocycle of 12 members.…”
mentioning
confidence: 99%